Unnecessary or Negligent? A Look into the Regulation of Non-Surgical Cosmetic Intervention in Europe: TCD Dermatological Society Essay Competition 2021 – Winner - Huwyler, Garrett (Trinity Student Medical Journal, 2022)
The regulation of medical devices and associated procedures is common across the globe, with country and regional variations directly impacting patient safety and ease of access. When considering non-surgical cosmetic interventions within Europe, the variations seen between member states of the European Union and that of the United Kingdom are quite dramatic. These regulations encompass procedures such as dermal fillers, botulinum toxin injections, and the application of lasers for skin rejuvenation treatments. Currently, the regulations in the European Union place an emphasis on quality control and safety for the products used by classifying them as medical devices and enforcing medical licensing requirements for their application. In contrast, the United Kingdom lacks regulation around both quality control and licensing requirements, placing patients at an increased risk for harm. This discussion recognises that patient autonomy and freedom of choice are key principles to be protected within this field, yet emphasis should also be placed on the proper regulation of expert practitioners and on the need for safe medical devices. The regulation of non-surgical cosmetic interventions holds substantial value for societal good, with an increase in safety, efficacy, accountability, and ultimately, patient well-being.